Tubulocystic renal cell carcinoma: Case report and literature review - Yun-Shen Ding; Yi-Han Wang; Feng Liu (Urology Case Reports)
To optimize the diagnosis and treatment of Tubulocystic renal cell carcinoma, we present our experience with a case of it and review the literature. Tubulocystic renal cell carcinoma (TRCC) is a rare subtype of renal carcinoma with distinctive histological and molecular characteristics. This study provides a comprehensive analysis of TRCC, focusing on its pathological features, diagnostic criteria, and potential molecular mechanisms. The findings highlight the unique histological architecture and biological behavior of TRCC, distinguishing it from other renal cell carcinomas. Advanced imaging techniques and molecular biomarkers play a pivotal role in its accurate diagnosis.